A Concept for Set‐based Design of Verification Strategies. Issue 1 (11th April 2023) - Xu, Pen; Salado, Alejandro
ABSTRACT: In current practice, a verification strategy is defined at the beginning of an acquisition program and is agreed upon by customer and contractor at contract signature. Hence, the resources necessary to execute verification activities at various stages of the system development are allocated and committed at the beginning, when a small amount of knowledge about the system is available. However, contractually committing to a fixed verification strategy at the beginning of an acquisition program fundamentally leads to suboptimal acquisition performance. Essentially, the uncertain nature of system development will make verification activities that were not previously planned necessary and will make some of the planned ones unnecessary. To cope with these challenges, this paper presents an approach to apply set‐based design to the design of verification activities to enable the execution of dynamic contracts for verification strategies, ultimately resulting in more valuable verification strategies than current practice.